A implementação da Lei de Cotas na Universidade Federal do Acre entre 2013 e 2014: percursos, apoio e inserção social - Monteiro, Adriana Vilhena (2023)
The objective of this research was to analyze the implementation of the quota law at the Federal University of Acre from 2013 to 2014, focusing on the historical itineraries covered in its implementation, the repercussions of institutional support at UFAC and the lessons learned about social inclusion of quota students, after the implementation of Law nº 12.711/2012. The methodological course consists preliminarily of a bibliographic survey in the specialized literature on the subject and through the Bank of CAPES and BDTD at the level of theses and dissertations comprising works on the institutional locus. A qualitative approach and data treatment were used through content analysis based on the works of Bardin (2011), concerning the documentation studied. The procedures used for data collection included: 1. Selection of institutional documentation within the selected range; 2. Analysis of the predominant actions regarding the implementation of the Quota Law at UFAC regarding: a) paths, b) support and c) social insertion. The study showed that UFAC immediately adhered to the process of implementing the Quota Law at an institutional level, however, this law, which changed the entire scenario of social diversity at the university, was only debated within the scope of its University Council, a more extensive and prior definition of its purposes and standardization of its structure and functioning on campus did not happen, although institutional support was provided. As for the result of social inclusion, it was noticed that the law applied to the university made it possible for minority groups to benefit and programs and student assistance actions were created and implemented to welcome quota students, however, there are still those not included in the broader spectrum of Brazilian education.